Epidemiology and definition of PPH worldwide - Bláha, Jan; Bartošová, Tereza (Best practice & research. Clinical anaesthesiology, 2022)
Postpartum/peripartum hemorrhage (PPH) is an obstetric emergency complicating 1-10% of all deliveries and is a leading cause of maternal mortality and morbidity worldwide. However, the incidence of PPH differs widely according to the definition and criteria used, the way of measuring postpartum blood loss, and the population being studied with the highest numbers in developing countries. Despite all the significant progress in healthcare, the incidence of PPH is rising due to an incomplete implementation of guidelines, resulting in treatment delays and suboptimal care. A consensus clinical definition of PPH is needed to enable awareness, early recognition, and initiation of appropriate intensive treatment. Unfortunately, the most used definition of PPH based on blood loss ≥500 ml after delivery suffers from inaccuracies in blood loss quantification and is not clinically relevant in most cases, as the amount of blood loss does not fully reflect the severity of bleeding.
Keywords: rizikové faktory; Peripartum Period; Maternal Mortality; peripartální období; Risk Factors; Incidence; lidé; Female; Pregnancy; poporodní krvácení; těhotenství; incidence; mateřská mortalita; Postpartum Hemorrhage; ženské pohlaví; Humans